Pengembangan Lembar Kerja Elektronik Siswa Berbentuk Inkuiri Terbimbing untuk Mendorong Kemampuan Berpikir Kreatif dan Kolaborasi Siswa - Bob Widodi; Wipsar Sunu Brams Dwandaru; Pascasie Nyirahabimana (JPPS (Jurnal Penelitian Pendidikan Sains), 2025)
Objective: This study aims to develop a guided inquiry–based Electronic Student Worksheet (ESW) and analyze its effectiveness in improving high school students’ creative thinking and collaboration skills, two essential competencies required in 21st–century learning. Method: The research employed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The product was validated by material, media, and language experts. A one-group pretest–posttest quasi-experimental design was implemented with 30 Grade XI students. Data were collected using a validated creative thinking test and collaboration observation sheet. Normality tests and paired sample t-tests were used for data analysis, followed by effect size calculations.  Results: The developed ESW obtained an average feasibility score of 72.75%, categorized as “eligible.” The creative thinking test and collaboration observations were also validated with scores of 71.25% and 66.25%, respectively, both in the “valid” category. Implementation results showed a significant improvement in creative thinking (from 3.33 to 6.97; p < 0.05; Cohen’s d = 1.08, large effect) and collaboration skills (from 12.83 to 16.23; p < 0.05; Cohen’s d = 1.44, very large effect).  Novelty: This study integrates the guided inquiry model directly into a digital ESW, producing substantial learning gains in two higher-order competencies simultaneously creative thinking and collaboration. Unlike previous studies that developed conventional or non-inquiry ESWs, this research demonstrates that inquiry-driven digital worksheets can generate strong cognitive and social skill enhancement in a single learning instrument.